Antecedents of patient health engagement in the radiotherapy service (evidence from Indonesia) - Anthony Kasena; Ferdi Antonio (AOSIS, 2023)
Background: Private radiotherapy (RT) facilities in emerging countries are growing with cancer incidence. Private healthcare providers must provide better care based on patient perspectives to reach more patients. Aim: This study investigated the relationship between antecedents of patient health engagement (PHE) with revisit intention (RVI) and intent to recommend (ITR) in private RT facilities. Setting: The survey was conducted in a private hospital with a RT service in Central Java province, Indonesia. Methods: A quantitative, cross-sectional design with a purposive sampling method was used. Patient questionnaire survey modified from validated self-administered radiotherapy experience (RTEQ) and PHE questionnaire were used to collect data. Partial least squares-structural equation modelling was used to analyse the data. Results: In this study, 173 respondents consented to participate, which demonstrated that seven of the eight experience antecedents of PHE measured by reliable and valid RTEQ and were significantly related to PHE (p-value 0.05). At the same time, the degree of PHE has a significant relationship with RVI and ITR (p-value 0.05). Conclusion: Patient informational needs elements from the patient experience, followed by situational repose, were shown to have a prominent relation to PHE. The management of private RT facilities needs to focus more on these elements to encourage PHE to establish hospital performance. Contribution: The findings denote that six elements of RTEQ relate to PHE and further hospital outcomes. Hospital management could utilise this approach to improve the quality of care in RT facilities, specifically in private hospitals in emerging countries.